Management of pulmonary toxicity associated with immune checkpoint inhibitors. (6th November 2019) - Delaunay, Myriam; Prévot, Grégoire; Collot, Samia; Guilleminault, Laurent; Didier, Alain; Mazières, Julien
Immunotherapy has become a standard of care in oncology, following the recent approvals of cytotoxic T-lymphocyte-associated protein-4 and programmed cell death-1 inhibitors in lung cancer, melanoma, renal cell carcinoma, Hodgkin's lymphoma, bladder, head and neck cancers. Besides their efficacy, these agents also generate specific immune-related adverse events. Due to the increasing prescription of immune-checkpoint inhibitors, the incidence of immune toxicity will continue to rise. The awareness of immune-related adverse events is key to ensuring both diagnosis and management of the possible serious adverse events. Although severe immune-related adverse events remain rare, they can lead to discontinued treatment or to death if they are not forecasted and managed properly. Even if lung toxicity is not the most frequent adverse event, it remains critical as it can be life-threatening. Herein, the main aspects of pulmonary toxicity are reviewed and guidelines are also proposed in order to manage the possible side-effects. Immune-related lung toxicity can be life-threatening. Early recognition and management including CT scan and bronchoscopy should be encouraged. Treatment mainly relies on steroids. In addition, re-challenge should be discussed in multidisciplinary boards. http://bit.ly/2WNYH8I